The Role of Integrated Quality Management and Innovation on Improving Company Performance - Mochamad Fauzan; Dessy Isfianadewi (International Journal of Economics, Business and Innovation Research, 2025)
This study examines the impact of Total Quality Management (TQM) on the performance of micro, small, and medium-sized Batik SMEs in Klaten, with innovation as an intervening variable. Using a quantitative approach and Partial Least Squares Structural Equation Modelling (PLS-SEM), data were collected through a survey of 121 Batik SME owners. The results show that TQM significantly influences both innovation and the performance of Batik SMEs. Additionally, innovation fully mediates the relationship between TQM and SME performance. Implementing TQM practices helps drive innovation, which, in turn, enhances SME performance. This research contributes to the literature by addressing the gap in empirical studies on the connection between TQM, innovation, and SME performance in the Batik sector, especially in developing countries like Indonesia, where TQM practices are still emerging and focused primarily on product and process innovation.